Capsaicin and Its Human Therapeutic Development 2018
DOI: 10.5772/intechopen.78353
|View full text |Cite
|
Sign up to set email alerts
|

CAP and Metabolic Diseases: A Mini Review on Preclinical Mechanisms and Clinical Efficacy

Abstract: Capsaicin (CAP) is the chief active ingredient of natural chili peppers. It has culinary and medicinal benefits. CAP activates its receptor, transient receptor potential vanilloid subfamily 1 (TRPV1), which is expressed in the sensory and motor neurons, adipocytes, liver, vascular smooth muscle cells, neuromuscular junction, skeletal muscle, heart and brain. The specificity of CAP to activate TRPV1 is the fundamental mechanism for its medicinal benefits to treat pain, obesity, hypertension, and other diseases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…The common interactions of the vanillyl groups in CAP and Capsiate (L553, L515, and S512) could explain how the latter ligand can activate TRPV1. However, it is possible that the extra interactions displayed by the vanillyl group in Capsiate (N551 and T550) produce structural changes in TRPV1 different than those elicited by CAP, leading to the lower level of activation evinced through the physiologic and thermogenic actions in mice described previously [9,10,11]. Regarding CAP-β- d gluco, the low degree of activation displayed by this ligand can be attributed to its binding outside the binding channel.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The common interactions of the vanillyl groups in CAP and Capsiate (L553, L515, and S512) could explain how the latter ligand can activate TRPV1. However, it is possible that the extra interactions displayed by the vanillyl group in Capsiate (N551 and T550) produce structural changes in TRPV1 different than those elicited by CAP, leading to the lower level of activation evinced through the physiologic and thermogenic actions in mice described previously [9,10,11]. Regarding CAP-β- d gluco, the low degree of activation displayed by this ligand can be attributed to its binding outside the binding channel.…”
Section: Discussionmentioning
confidence: 89%
“…CAP-induced rise in intracellular Ca 2+ via TRPV1 is suggested to facilitate its thermogenic effect [10]. Also, clinical research has demonstrated the enhancement of energy expenditure in humans by CAP and Capsiate [11]. Although similar studies have been performed with several combinations of capsinoids and capsaicinoids in rodent models, such studies have used divergent doses and concentrations of these compounds [7,11], which make the interpretation of the results difficult and challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capsaicin (CAP) is a key ingredient of natural chili peppers. The benefits of CAP to treat neuropathic pain 13 , cancer 47 and metabolic syndrome 814 have been extensively researched in the recent years. Previous experimental studies using CAP patches applied locally on rats and rabbits suggest that CAP was safe and well tolerated 15 .…”
Section: Introductionmentioning
confidence: 99%